2015
DOI: 10.3390/su70912340
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Energy Portfolios for Small Island States

Abstract: Abstract:The study presents a cost effective electricity generation portfolio for six island states for a 20-year period . The underlying concept investigates whether adding sizeable power capacities of renewable energy sources (RES) options could decrease the overall costs and contribute to a more sustainable, indigenous electricity generation at the same time. Often, island states rely on fossil fuels which, apart from dependence on foreign resources, also includes an additional, significant transport cost. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The use of spatial analysis as decision support tools could support the definition of general rules for a more functional rural electrification plan at national level in Africa as other studies have demonstrated [28][29][30][31][32][33][34]. The georeferenced electrification tool aims to support the Burkina Faso government and development partners to define a coordinated planning for electrification, focusing on different technological choices.…”
Section: Rural Electrification Planning Tool: Leastcost Electricity Omentioning
confidence: 99%
“…The use of spatial analysis as decision support tools could support the definition of general rules for a more functional rural electrification plan at national level in Africa as other studies have demonstrated [28][29][30][31][32][33][34]. The georeferenced electrification tool aims to support the Burkina Faso government and development partners to define a coordinated planning for electrification, focusing on different technological choices.…”
Section: Rural Electrification Planning Tool: Leastcost Electricity Omentioning
confidence: 99%
“…Among others, [47] discusses the dependency of Mediterranean islands on fossil fuels and the underutilization of renewable energy source (RES) potential and discusses economic feasibility of RES. Long-term cost-benefit analyses are the main focus of [48] which also analyzes the potential effects of RES installations for small islands. A Caribbean use case with high RES penetration is elaborated by [49].…”
Section: Planning and Optimizationmentioning
confidence: 99%
“…Renewable energy (RE) targets pave the path for continuously increasing the share of clean technologies in national energy portfolios [1]. The number of countries adopting national policies has significantly increased during the last decade.…”
Section: Introductionmentioning
confidence: 99%